The Shifting Strategy of Taiwan’s New Southbound Policy (NSP) Programs - Siti Mufidah Ainun Nabila; Moh. Fathoni Hakim (Jurnal Sosial Humaniora Sigli, 2026)
This study examines how Taiwan’s New Southbound Policy (NSP) has evolved over two major phases: the education phase (2019–2025) and the economic phase (2016–2018). This study identifies the structural factors driving this strategic shift by employing an exploratory qualitative approach and analyzing official Taiwanese government documents. The findings indicate that Taiwan shifted its strategy toward soft power-based educational diplomacy due to constraints in economic performance, as evidenced by the declining share of exports to NSP partner countries. After initially prioritizing economic development, Taiwan gradually integrated higher education as a key focus through initiatives such as INTENSE, “study and stay,” and Mandarin Education 2025. When viewed through the lens of Joseph Nye’s concept of soft power, the second phase of the NSP presents education as a means of conveying values and fostering enduring cultural appeal. According to the study’s findings, the NSP’s transformation represents an adaptive response to both the limitations of traditional economic tools and domestic demographic pressures